The role of access to electricity, female education, and public health expenditure on female health outcomes: evidence from SAARC-ASEAN countries - Mohammad Mafizur Rahman; Khosrul Alam (BMC, 2021)
Abstract Background The importance of the status of female health should have research priority due to the unique medical needs of women. Hence this paper attempts to explore the nexus of access to electricity, female education, and public health expenditure with female health outcomes in the SAARC-ASEAN countries. Methods Using the data of 2002-2018, and applying the cross-sectional dependence test, Modified Wald test, Wooldridge test, the Panel corrected standard error (PCSE) model, the Feasible generalized least square (FGLS) model, and the pair-wise Granger causality test, the robust outcomes on female health are found. Results Access to electricity, female education rate, public health expenditure, economic growth, and immunization rate, all have a positive effect on female life expectancy at birth, and a negative effect on the female adult mortality rate. The urbanization rate has a significantly positive impact on female life expectancy at birth but an insignificant impact on female adult mortality rate. The one-way causal relationship between the variables are also revealed. Conclusions All the results are rational and have important milestone for the health sector. The health status of females should be improved and protected by formulating effective policies on access to electricity, female education, public health expenditure, immunization, economic growth, and urbanization.